1996
DOI: 10.1515/mamm.1996.60.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological responses to a subterranean habitat; a Bathyergid perspective.

Abstract: Sunwmiy. -Mammals that lead a strictly subterranean existence encounter very different physiological problems to those living above the ground. While an underground habitat effectively shields the inhabitants from extreme climatic stresses and predation, it also provides a dark and poorly ventilated environment. Specialized physiological features in this milieu include altered sensory perception, vitamin D status and concomitant mineral metabolism, relaxed thermoregulation and specialised gut function. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
(59 reference statements)
1
31
0
Order By: Relevance
“…Additionally, NMRs have high hematocrit levels, and their hemoglobin has a higher affinity for oxygen compared with aboveground-dwelling mammals (6,20). Even after being housed under normoxic conditions in captivity for more than 30 years, NMRs maintain hematocrits of ϳ50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NMRs have high hematocrit levels, and their hemoglobin has a higher affinity for oxygen compared with aboveground-dwelling mammals (6,20). Even after being housed under normoxic conditions in captivity for more than 30 years, NMRs maintain hematocrits of ϳ50%.…”
Section: Discussionmentioning
confidence: 99%
“…Living communally in deep (ϳ2 m) underground colonies with up to 300 individuals (4), NMRs must contend with atmospheric oxygen contents ranging from as low as 4% in the nests to 20% in superficial foraging burrows. Moreover, underground atmospheres can be very humid and high in carbon dioxide (6). NMRs exhibit many adaptations to this hostile milieu, including a low basal metabolic rate (9,15), thermolability (9), and extreme tolerance to hypercapnia and variable oxygen availability (12,25,35).…”
mentioning
confidence: 99%
“…Living underground protects the mole-rats from extreme changes in weather and temperature in addition to protection from predation. However, it poses other challenges associated with life in a dark dank environment with poor gas and heat exchange [13]. Not surprisingly, they therefore have low basal metabolic rates and resting body temperatures [14].…”
Section: Naked Mole-rats and Aging Researchmentioning
confidence: 99%
“…However, pregnancy-related growth still contributes most to phenotypic changes as spine length increases with each pregnancy until an asymptote is reached (O'Riain et al, 2000;Henry et al, 2007) (C.M.D.-C., unpublished). Since both removal from reproductive suppression and pregnancy cause lumbar spine expansion, it is plausible that both events rely on similar hormonal mechanisms -possibly estrogens -to facilitate growth (Buffenstein, 1996;Bowman and Miller, 1997;Eastell, 2005), but the exact endocrine mechanisms involved need to be elucidated. This puberty-like growth is eventually attenuated, as shown by the growth spurt pattern in the rate of spine elongation.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…Previous studies demonstrate that female mole-rats that successfully breed experience an elongation of the body caused by the expansion of the lumbar vertebrae (O'Riain et al, 2000;Jarvis et al, 1991;Buffenstein, 1996;Henry et al, 2007). Additional data collected by Henry et al have shown that lumbar spine growth increases during pregnancy and is attenuated in the period after or between pregnancies (Henry et al, 2007).…”
Section: Introductionmentioning
confidence: 99%